Influência da infecção endodôntica e/ou periodontal associadas à diabetes na quantificação sérica da citocina pró-inflamatória IL-17 e na glicemia de ratos Wistar - Samuel, Renata Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of the study was to evaluate the influence of periapical lesions and/or periodontal disease on the IL-17 serum and dosage glycemic a rat model of diabetes mellitus. Eighty male Wistar rats were divided into eight groups of ten animals each: normal rats (G1), rats with pulpal infection (G2), rats with periodontal disease (G3), rats with pulpal infection and periodontal disease (G4), diabetic rats (G5), diabetic rats with pulpal infection (G6), diabetic rats with periodontal disease (G7), diabetic rats with pulpal infection and periodontal disease (G8). Diabetes was induced using streptozotocin, pulpal infection were induced by dental pulp exposure to the oral environment and the periodontal disease by periodontal ligature. Blood glucose was measured by means of a perforation in the tail of the animal after 0, 6 and 30 days post-operative. The animals were sacrificed after 30 days and the IL-17 levels were measured by ELISA. The total assessed values was tabulated according to each experimental group and statistically analyzed by analysis of variance (ANOVA) followed by Tukey test (p<0.05). Glucose levels were higher in diabetic rats compared to control rats at 6, and 30 days (p <0.05). However, at 30 days, and among the groups of diabetic rats, it was observed that the presence of periodontal infection alone (G7) or associated with endodontic (G8) increased significantly the blood glucose compared to diabetic rats without oral infections (G5 ) (p <0.05). The presence of systemic disease diabetes was not able to increase the level of serum IL-17 (p <0.05). However, the presence of the associated oral infections (G4, G8) significantly elevated the serum level of IL-17, regardless of the presence of diabetes (p <0.05). It can be concluded that the endodontic infection when associated with periodontal disease may increase blood glucose levels in diabetic rats and the serum level of IL-17 in normoglycemic or diabetic rats

O objetivo deste trabalho foi avaliar a influência da periodontite apical e/ou doença periodontal associadas à diabetes na quantificação sérica da citocina pró-inflamatória IL-17 e na glicemia. Foram utilizados 80 ratos da linhagem Wistar divididos em 8 grupos de 10 ratos: G1 - ratos normoglicêmicos ; G2 - ratos com infecção endodôntica; G3 - ratos com infecção periodontal; G4 - ratos com infecção endodôntica e periodontal; G5 - ratos diabéticos; G6 - ratos diabéticos com infecção endodôntica; G7 - ratos diabéticos com infecção periodontal; G8 - ratos diabéticos com infecção endodôntica e periodontal. A diabetes foi induzida pela aplicação de estreptozotocina via veia peniana, cujo desenvolvimento da doença foi confirmado no sexto e último dia do experimento pela avaliação glicêmica no sangue por meio de uma punção na extremidade da cauda do animal, seguida de pequena compressão para a obtenção de uma gota de sangue. A infecção endodôntica foi induzida pela exposição pulpar do primeiro molar superior direito. A infecção periodontal foi induzida por meio da confecção de uma amarria junto ao colo dentário do segundo molar superior esquerdo. Com 30 dias pós-operatórios foi realizada a glicemia novamente e a coleta de sangue pela punção cardíaca para a quantificação da citocina IL-17 empregando a técnica de ELISA de captura. Os resultados foram analisados do pelo teste de análise de variância e teste de Tukey (p<0,05). O nível glicêmico foi maior em ratos diabéticos quando comparados com ratos controle aos 6 e 30 dias (p<0,05). Entretanto, aos 30 dias nos grupos de ratos diabéticos, observou-se que a presença da infecção periodontal isolada (G7) ou associada à endodôntica (G8) aumentou de forma significante a glicemia quando...
Keywords: Diabetes; Interleucina-17; Glicemia